Optimizing toll collector scheduling using goal programming / Diana Sirmayunie Mohd Nasir ... [et al.] - Mohd Nasir, Diana Sirmayunie; Abu Hasan, Suzanawati; Shafii, Nor Hayati; Marhanith, Noreena Ayu (Universiti Teknologi MARA, Perak, 2023)
The importance of providing an effective shift work schedule cannot be overstated, particularly when considering the continuous 24-hour service requirement. Each employee has their own schedule preferences, and while some positions offer just one or two shifts, others encompass three separate scheduling periods within a day. The issue arises when these varying schedules lead to disparities among workers of toll collectors in terms of overall time spent, creating an inequitable situation. Unfortunately, the objectives of the Bentong Toll Plaza and the preferences of the toll collectors have not been in harmony, which could potentially impact the performance and worklife balance of the toll collectors. The ongoing challenge faced by managers is the selection of the most suitable shift schedule. Thus, this study aims to introduce a new cyclic scheduling approach to streamline the task of creating schedules at Bentong Toll Plaza. Goad programming is applied to meet the requirements of four rigid constraints and three flexible constraints. The initial schedule is used for the first 15 days and then systematically rotated for another 15 days until all toll collectors have experienced all 15 schedule sets. This scheduling process was facilitated through the utilization of Lingo software, resulting in an optimized 15-day shift schedule for toll collectors. The third goal was achieved, which was that each toll collector was assigned the same amount of work. However, the first and second goals are not entirely met, but this has a minimal impact on the toll collectors due to the schedule rotation. In conclusion, it has been proven that the generated schedule pattern provides a better schedule in terms of providing each toll collector with the same total number of shifts and off days.